2022
DOI: 10.1039/d2qo00312k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidative dearomatization of 2-arylthiophenes

Abstract: Herein we report a green and sustainable electrochemical oxidative dearomatization of 2-arylthiophenes. The variation of substitution patterns affords easy access toward both the C2/C3 and C2/C5 difunctionalized dearomative products. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…They discovered that the C2 position of thiophenes 122 is more dynamic than the C3 position to accomplish the electrochemical oxidative dearomatization, affording a wide array of C2/C5 difunctionalized 2‐arylthiophines 123 and C2/C3 difunctionalized products 124 by changing the substitution patterns (Scheme 48). [58] These electrochemical oxidative methods would complement previous approaches and support expansion of the toolbox for the dearomatization of aromatic compounds. We believe it will be sustainable research in the future.…”
Section: Electrochemical Oxidation Dearomatization Reactionsmentioning
confidence: 94%
“…They discovered that the C2 position of thiophenes 122 is more dynamic than the C3 position to accomplish the electrochemical oxidative dearomatization, affording a wide array of C2/C5 difunctionalized 2‐arylthiophines 123 and C2/C3 difunctionalized products 124 by changing the substitution patterns (Scheme 48). [58] These electrochemical oxidative methods would complement previous approaches and support expansion of the toolbox for the dearomatization of aromatic compounds. We believe it will be sustainable research in the future.…”
Section: Electrochemical Oxidation Dearomatization Reactionsmentioning
confidence: 94%
“…Among various aromatics and heteroaromatics, , the dearomative spirocyclization of thiophenes is underdeveloped, probably due to their relatively high resonance stabilization energy (∼22 kcal mol –1 ). For instance, Wright and co-workers have shown that the electrochemical dearomative spirocyclization of the C2-tethered furan readily proceeded with C2-spirocyclization (Scheme A) . When it is transferred to the analogous thiophene derivative, however, a nonselective C2 and C3 Friedel–Crafts type alkylation took place, followed by downstream chemical and electrochemical transformations, to generate both C3-annulation and C2-spirocyclization products.…”
mentioning
confidence: 99%
“…Notably, the incorporation of an extra bromo group into the thiophene moiety ( 39 ) readily afforded the dearomative thiophenone ( 40 ), probably via the hydrolysis of a dihydrothiophene diacetate intermediate (Scheme , eq 1). , The ( p -tolyl)­acetic acid derivative ( 41 ), however, did not proceed with the electrochemical dearomative spicrocyclization but gave the oxindole scaffold ( 42 ), likely via a sequential electrochemical ortho amination and benzylic oxygenation (eq 2). The thiophenone ( 40 ) and oxindole ( 42 ) products were both confirmed by X-ray crystallographic analyses…”
mentioning
confidence: 99%